2014
DOI: 10.1080/14783363.2014.918707
|View full text |Cite
|
Sign up to set email alerts
|

Framework for the generic process of diagnosis in quality problem solving

Abstract: This study looks at the problem of determining root causes, presenting an artefact (Causal Determinant) composed of procedures and coded algorithms in software for the purpose of identifying the potentially most relevant cause for a given effect. The design science research approach was used to develop, test and prove the utility of the Causal Determinant artefact. A total of 95 cases were studied at 32 small, medium-sized and large companies. An analysis of the perception of these users showed the easy operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Concerning software, Sanches et al (2015) demonstrate the practical benefits of using the artifact proposed by the research. The research contributions were perceived and identified by the users, who highlighted the practical nature of the method and the ability to identify the root cause of a given problem by the software (based on the prioritization matrix) as a logical and consistent result for predictive purposes.…”
Section: Research Contributionsmentioning
confidence: 84%
See 3 more Smart Citations
“…Concerning software, Sanches et al (2015) demonstrate the practical benefits of using the artifact proposed by the research. The research contributions were perceived and identified by the users, who highlighted the practical nature of the method and the ability to identify the root cause of a given problem by the software (based on the prioritization matrix) as a logical and consistent result for predictive purposes.…”
Section: Research Contributionsmentioning
confidence: 84%
“…Relating to the problem class "modeling and process improvement," he classified the articles by Sanches et al (2015); Anke (2019); Saraswat et al (2014). Sanches et al (2015) analyze a problem to determine the root causes, presenting an artifact composed of procedures and algorithms (coded in software), aiming to identify the potentially most important cause for a given effect. Already, in Anke's research (2018), he proposes a method for the integrated financial evaluation of intelligent design services.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To Sanches et al (2015), the "Emach expresses the meaning and power of the factor in the cause and effect (C-E) relationship" (p. 8). The Emach calculation enables information regarding the "degree of causality": causal factors are negative and effect factors are positive.…”
Section: Open Accessmentioning
confidence: 99%